2002
DOI: 10.1002/1521-4087(200203)27:1<34::aid-prep34>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research of the Effects of Superfine Aluminum Powders on the Combustion Characteristics of NEPE Propellants

Abstract: The combustion behavior of grading aluminum powders containing superfine aluminum powder (SAl) in NEPE propellant has been studied by several kinds of experimental techniques. The results indicate that the usage of grading aluminum powders containing SAl can effectively improve the combustion characteristics of NEPE propellant and the combustion efficiency of aluminum. The reason is that SAl has the different combustion and thermochemical properties from those of generally powdered aluminum (Al). SAl is inclin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…Although Al powder has a high energy density, there are still some defects in the combustion process: the solid Al 2 O 3 film on the surface of Al powder causes a long ignition delay, and it tends to agglomerate during the combustion process, resulting in long combustion time and incomplete combustion, and the products are easily agglomerated, etc. These problems greatly limit the further improvement of propellant performance [5][6][7][8][9][10][11][12]. Studies have shown that the oxidation activity and reaction completeness of aluminium-based alloy powders are significantly better than that of single Al powders.…”
Section: Introductionmentioning
confidence: 99%
“…Although Al powder has a high energy density, there are still some defects in the combustion process: the solid Al 2 O 3 film on the surface of Al powder causes a long ignition delay, and it tends to agglomerate during the combustion process, resulting in long combustion time and incomplete combustion, and the products are easily agglomerated, etc. These problems greatly limit the further improvement of propellant performance [5][6][7][8][9][10][11][12]. Studies have shown that the oxidation activity and reaction completeness of aluminium-based alloy powders are significantly better than that of single Al powders.…”
Section: Introductionmentioning
confidence: 99%
“…Al is a prospective energetic fuel that exhibits a considerable advantage due to its high energy, safe byproducts, and low preparation cost. It is frequently utilized as a highenergy propellant component [3][4][5][6][7]. Al has undergone substantial research as a powder fuel for new propulsion systems with the development of powder ramjet technology [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Metal fuel [1][2][3][4][5] (such as aluminum, magnesium, iron, boron, beryllium, and lithium) is one of the new energy sources to replace the traditional fuel, which can significantly increase the energy and density of the power system of the land and water transportation pressure), and releases a large amount of energy. The energy density (taking aluminum water reaction metal fuel as an example) is 4-6 times of that of fuel oil, and there is no waste gas pollution, which can make up for the shortage of current energy and has a broad application prospect [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%